Advanced Adrenocortical Carcinoma – What to do when First-Line Therapy Fails? - Megerle, Felix; Kroiss, Matthias; Hahner, Stefanie; Fassnacht, Martin (Experimental and Clinical Endocrinology & Diabetes, 2019)
Adrenocortical carcinoma is a rare endocrine malignant disease with a generally unfavorable but heterogeneous prognosis. Although even in advanced stages a subset of patients experiences long-term disease stabilisation, effective systemic treatment options are limited. Mitotane is the only approved drug and the combination of etoposide, doxorubicin and cisplatin (plus mitotane) is currently considered as treatment standard for advanced adrenocortical carcinoma based on the results of a large randomized phase III trial. However, progression-free survival is often limited and further treatment options are frequently needed. Here we summarize the current knowledge about second and third-line therapeutic modalities (local and systemic) in advanced disease. Following the recent ESE-ENSAT guidelines local therapies play an important role for these patients. Regarding systemic therapies the best data are available for gemcitabine+capecitabine or streptozotocin (both with or without mitotane). Furthermore, we introduce our own approach to patients with advanced adrenocortical carcinoma based on our experience as a large multidisciplinary clinic dedicated to the care of patients with this orphan disease.
Keywords: adrenal cancer; ACC; second line therapy